Characterization of radiographic features of consecutive lumbar spondylolisthesis. Issue 46 (November 2016) - Sun, Yapeng; Wang, Hui; Yang, Dalong; Zhang, Nan; Yang, Sidong; Zhang, Wei; Ding, Wenyuan
Abstract : Abstract: Radiographic features of consecutive lumbar spondylolisthesis were retrospectively analyzed in a total of 17 patients treated for this condition at the Third Hospital of Hebei Medical University from June 2005 to March 2012. To investigate the radiographic features, pelvic compensatory mechanisms, and possible underlying etiologies of consecutive lumbar spondylolisthesis. To the best of our knowledge, there is no previous report concerning the characteristics of consecutive lumbar spondylolisthesis. The Taillard index and the lumbar lordosis (LL), pelvic incidence (PI), sacrum slope (SS), and pelvic tilt (PT) were determined on lateral X-ray images, and the angular displacement was analyzed on flexion–extension X-ray images. Correlation between LL and various pelvic parameters and correlation between Taillard index and angular displacement were assessed by Pearson correlation analysis. A total of 20 cases of isthmic spondylolisthesis and 14 of degenerative spondylolisthesis were retrospectively studied in 17 patients. The Taillard index and the angular displacement in the lower vertebrae were both larger than those in the upper vertebrae. Statistical analysis revealed that LL was correlated with PI and PT, whereas PI was correlated with PT and SS. However, no correlation was identified between Taillard index and angular displacement. In consecutive lumbar spondylolisthesis, the degree of vertebral slip and the angular displacement of the lower vertebrae were both greater than those of the upper vertebrae, indicating that the compensatory mechanism of the pelvis plays an important role in maintaining sagittal balance.